O papel do Estado na proteção social: os caminhos e descaminhos da política pública previdenciária brasileira - Marília Carvalho de Oliveira (2020)
The purpose of this dissertation was to analyze the Brazilian Social Security of the Brazilian State in the promulgation of the 1988 Constitution, investigating the constitutionality of the recent proposal for social security reform, approved in Constitutional Amendment 103 of 2019, in November of that year. It was questioned whether the reform was dismantling the Social Security System and favoring a Private Pension System, and whether this state policy found support in the Federal Constitution. For this purpose, the political and world history of Social Security, the political history of Brazilian Social Security, the existing social security systems in the social security literature, the Social Security System in the Federal Constitution of 1988, with its premises and foundations and its reforms were analyzed. until the approval of this latest social security reform. Then, the analysis of the deficit discourse of the System and the influence of international organizations in the pension policy of the countries, including Chile, pioneer in the implementation of a Pension System under the capitalization regime, and the consequences of this choice. The theoretical framework of the research was the fundamental principle of Social Security, that is, solidarity, the foundation of the protection system, and the hypothesis initially presented was that the social security reform proposed by the Federal Government ignores solidarity and social co-responsibility, causing the dismantling of the Brazilian Social Security System, an important fundamental right in complying with the fundamental principles, foundations and objectives of the State, making the development and social justice foreseen in the foundations of the Brazilian Democratic State of Law impossible.